If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(t + -8) + -1(t + 3) = 1 Reorder the terms: -3(-8 + t) + -1(t + 3) = 1 (-8 * -3 + t * -3) + -1(t + 3) = 1 (24 + -3t) + -1(t + 3) = 1 Reorder the terms: 24 + -3t + -1(3 + t) = 1 24 + -3t + (3 * -1 + t * -1) = 1 24 + -3t + (-3 + -1t) = 1 Reorder the terms: 24 + -3 + -3t + -1t = 1 Combine like terms: 24 + -3 = 21 21 + -3t + -1t = 1 Combine like terms: -3t + -1t = -4t 21 + -4t = 1 Solving 21 + -4t = 1 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -4t = 1 + -21 Combine like terms: 21 + -21 = 0 0 + -4t = 1 + -21 -4t = 1 + -21 Combine like terms: 1 + -21 = -20 -4t = -20 Divide each side by '-4'. t = 5 Simplifying t = 5
| n=0.04x-78.70 | | -17=x+23 | | 8a-6=6y+2 | | 28x^2+19x-5=-8 | | 0.33(10x+27)=-0.2(18.33x+25) | | 0.7(3x-20)=22-3.9x | | 180-2x=34x+24 | | 11n-9=6n+29 | | 26x^2-9=0 | | 1.6(1.5x+7.5)=0.6(6x+30) | | y=.75x-2 | | (-2(14x-2))=((9x+8)(x-3)) | | -22-10x=10x-18 | | 28t^2-46+16=0 | | 9x^2-7x-28=0 | | -3x-8=10 | | .4(3x+8)=.2(x+5) | | 123-4x=5x+15 | | 7x+5-4x+7= | | 22x-8-12x+2=26x-3-16x+17 | | 6-2(3x-4)=8 | | p^2+5p=0 | | 6(2x-4)+2(x+3)=7 | | 28c^2-66c+36=0 | | 4n^2+3n-10=0 | | 1-.0105263x^2=0 | | 11x^2-29x=0 | | 8+32=80 | | 17*5076.5625= | | 8+32= | | 1+4=10 | | x+(x+18)=46 |